2012
DOI: 10.1016/j.jcrs.2012.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Corneal power estimation for intraocular lens power calculation after corneal laser refractive surgery in Chinese eyes

Abstract: The algorithm was a relatively reliable method in IOL power calculation after corneal refractive surgery in Chinese eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…There have been reports in which the first 2 techniques were applied to obtain the ratio of anterior corneal curvature to posterior corneal curvature, and the keratometric index was calculated regarding the total corneal power based on Gaussian optics formula as a benchmark. [ 1 , 5 , 6 , 17 ] However, to the best to our knowledge, until now there have been no reports on the keratometric index calculated by data derived from RTVue FD-OCT (RTVue, Optovue, Inc.).…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports in which the first 2 techniques were applied to obtain the ratio of anterior corneal curvature to posterior corneal curvature, and the keratometric index was calculated regarding the total corneal power based on Gaussian optics formula as a benchmark. [ 1 , 5 , 6 , 17 ] However, to the best to our knowledge, until now there have been no reports on the keratometric index calculated by data derived from RTVue FD-OCT (RTVue, Optovue, Inc.).…”
Section: Introductionmentioning
confidence: 99%
“…18,19 IOL power calculation using adjusted corneal power calculated with the variable keratometric index also improved refractive outcomes in eyes with a history of previous refractive corneal surgery after cataract surgery. [20][21][22] There were no improvements in refractive outcomes when we applied the true net power and total corneal refractive power from Pentacam directly to IOL power calculation despite IOL constant optimization; instead, outcomes were worse in many cases. In line with this study, previous studies also found no superiority using the corneal power derived from both the anterior and posterior corneal measurements of a single Scheimpflug camera relative to using simulated K in IOL power calculation for normal eyes.…”
Section: Discussionmentioning
confidence: 97%
“…However, the constants in their study were not optimized for each IOL model. Jin et al [22] found that when the Koch–Maloney method was used in Chinese eyes, an offset value of −6.2 was more appropriate than −6.1. However, in the present study, the results from IOL-Master did not show the same tendency.…”
Section: Discussionmentioning
confidence: 99%